Knowledge of caregivers for the prevention of injuries among children in day-care centres, in Putrajaya and Selangor, 2016 - Hassan, Nabiha Gul; Kadir @ Shahar, Hayati; Abdul Rahman, Hejar (International Journal of Children, Women, Elderly and Disable People, 2017)
Injuries among children are one of the leading causes of morbidity and mortality world-wide. The need for out-of-home care for children has increased substantially due to the recent increase of female participation in the work force. All children deserve the right to a safe environment and therefore caregivers given the task of caring for children in day-care centres must be qualified and able to protect them from injury. This study is aimed to identify the knowledge of caregivers that affect safety and injury prevention in licensed day-care centres in Malaysia. A cross-sectional study design was carried out among 399 participants in licensed day-care centres in a total of 12 districts across Putrajaya and Selangor. Stratified random sampling method was used to collect information on socio-demographic, socio-economic factors through the use of validated self-constructed, self-administered questionnaires between September 2015 and May 2016. Only caregivers who were in direct contact with children were eligible to participate in the study. Data was analyzed using, descriptive, bivariate and multivariate data analysis by SPSS™ (version 21). The analysis was carried out using Chi-square test and Multiple Logistic Regression. The study response rate was 89.47%. Caregivers were found to have a mean knowledge score of 66.33 ± 0.57. Significant predictors of knowledge were caregivers who had an education level of SPM or less (AOR=3.487, 95% CI 2.19 - 5.55), caregivers under the age of 25 (AOR=0.119, 95% CI 1.19 - 4.67), and caregivers who were unmarried (AOR= 2.077, 95% CI 1.126 - 3.828). In conclusion, we can increase awareness of the factors that affect knowledge for the prevention of injury among caregivers in day-care centres. This information can help us hire well-equipped caregivers and build safer day-care centres for children.